Huda F cares? - Fahmy, Huda (Dial Books, an imprint of Penguin Random House LLC, 2023)
In this laugh-out-loud funny sequel to "Huda F Are You?," the Fahmys are off to Disney World, but self-conscious Huda worries her family will stand out too much. Huda and her sisters can't believe it when her parents announce that they're actually taking a vacation this summer... to DISNEY WORLD! But it's not quite as perfect as it seems. First Huda has to survive a 24-hour road trip from Michigan to Florida, with her sisters annoying her all the way. And then she can't help but notice the people staring at her and her family when they pray in public--there's not as many Muslim families around like in her hometown of Dearborn. It's a vacation of forced (but unexpectly successful?) sisterly bonding, a complicated new friendship, a bit more independence, and some mixed feelings about her family's public prayers. Huda is proud of her religion and who she is, but she still sure wishes she didn't care so much what other people thought.